Hyperaccumulator plants of the Keban Mining district and their possible impact on the environment - Sağıroğlu, Ahmet; Şaşmaz, Ahmet; Şen, Özlem (My University, 2006)
Metal intake abilities of Euphorbia macroclada, Verbascum cheiranthifolium Boiss and Astragalus gummifer, which are common and native throughout Turkey and similar locations, were studied in the heavily polluted Keban mining district in Elazig, Turkey. For this aim metal contents of dried plants and soil were determined and correlated. Soils of Keban area have higher than average values for soil, Mo, Cu, Pb, Zn, Ag, As and Cd contents. All the studied plants take up metals in high amounts - as high as hundreds of times more than averages for non-hyperaccumulator plants. Usually, higher plant metal contents are attained where higher soil metal contents exist. Enrichment factors, which are calculated by dividing metal contents of plant by metal contents of soil (= metal content of plant/metal content of soil), are higher in lower soil metal contents. Maximum metal contents in the shoots (as mg kg-1) and enrichment factors for Euphorbia are: Mo 260- 1.28, Cu 33-0.18, Pb 76-0.09, Zn 190-0.51, Ag 0.53-1.1, Mn 276-0.28, As 10.2-0.08, and Cd 0.20-0.13. For Verbascum: Mo 80-0.83, Cu 27-2.87, Pb 295-1.57, Zn 254-1.78, Ag 0.37-0.92, Mn 627-0.58, As 63.5-0.50 and Cd 0.59-1.25. For Astragalus’s gummufer: Mo 402-0.98, Cu 30-0.95, Pb 552-0.82, Zn 241- 0.31, Ag 0.54-0.64, Mn 1072-0.34, As 45.4-0.34 and Cd 0.34-0.44. All of the three plant species have enrichment factors exceeding hyperaccumulating criterion >1 for most of the elements investigated. Most of the hyperaccumulator values belong to Verbascum cheiranthifolium Boiss. Hyperaccumulating properties have been considered for reclamation of contaminated lands. This study claims that plants with high metal intake abilities escalate mobility of metals and increase contaminations on surface and subsurface.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Contaminated lands; Keban; Heavy metal; Hyperaccumulator plants